Search for pair production of third-generation scalar leptoquarks and top squarks in proton-proton collisions at v root s=8 TeV - (:unkn) unknown (ELSEVIER, 2014)
A search for pair production of third-generation scalar leptoquarks and supersymmetric top quark partners, top squarks, in final states involving tau leptons and bottom quarks is presented. The search uses events from a data sample of proton-proton collisions corresponding to an integrated luminosity of 19.7 fb(-1), collected with the CMS detector at the LHC with root s = 8 TeV. The number of observed events is found to be in agreement with the expected standard model background. Third-generation scalar leptoquarks with masses below 740 GeV are excluded at 95% confidence level, assuming a 100% branching fraction for the leptoquark decay to a tau lepton and a bottom quark. In addition, this mass limit applies directly to top squarks decaying via an R-parity violating coupling. lambda(') (333). The search also considers a similar signature from top squarks undergoing a chargino-mediated decay involving the Rparity violating coupling. lambda(')(3jk). Each top squark decays to a tau lepton, a bottom quark, and two light quarks. Top squarks in this model with masses below 580 GeV are excluded at 95% confidence level. The constraint on the leptoquark mass is the most stringent to date, and this is the first search for top squarks decaying via. lambda(')(3jk). (C) 2014 The Authors. Published by Elsevier B. V.
Keywords: CMS; Physics; Leptoquark; Top squark; SUPERSYMMETRY